Advantages and risks of nanotechnologies in cancer patients and occupationally exposed workers. (July 2014) - Lamberti, Monica; Zappavigna, Silvia; Sannolo, Nicola; Porto, Stefania; Caraglia, Michele
Abstract : Introduction: In recent years, different nanotechnology platforms for drug delivery in the area of medical biology have gained remarkable attention. Areas covered: Nanoparticles (NPs) used as drug delivery vehicles consist of different materials such as natural or synthetic polymers, lipids or metals. They have an ultra-small size, large surface area-to-mass ratio and high reactivity. Although there are many data on the advantages in terms of both higher efficacy and less adverse effects of nanodrugs, several recent findings have reported unexpected toxicities giving origin to nanotoxicology. Expert opinion: Despite the great promise that NPs show, few studies have examined the human body's reaction due to NP exposure in both patients and workers. To perform this type of evaluation, it is necessary to define an adequate index of exposure, and the measure of this index is representative of what the worker is breathing. The properties of the nanomaterials used for designing NPs, such as in the case of poorly biocompatible materials (carbon nanotubes or heavy metals), and their chemical composition (as in the case of liposomes) largely contribute in determining potential side effects. Awareness of the levels of particles, which can cause health effects, is necessary for the workers and exposed patients.